2021
DOI: 10.1177/08853282211025912
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor loaded macrophage-derived nanovesicles for inhibiting neuronal apoptosis after spinal cord injury

Abstract: Spinal cord injury (SCI) is an extremely destructive central nervous system lesion. Studies have shown that NGF can promote nerve regeneration after SCI. However, it cannot produce the desired effect due to its stability in the body and is difficulty in passing through the blood-brain barrier. In this study, we prepared nanovesicles derived from macrophage membrane encapsulating NGF (NGF-NVs) as a drug carrier for the treatment of SCI. Cell experiments showed that NGF-NVs were effectively taken up by PC12 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 41 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Nerve growth factor (NGF) is an important member of the neurotrophic factor family with important roles in neuron development, axon growth, neurotransmitter synthesis and apoptosis 220 . Xia et al 221 showed that NGF inhibited oxidative stress‐induced apoptosis in an in vitro model of SCI. NGF significantly activated the PI3K/AKT signalling pathway, promoted the expression of the anti‐apoptotic protein Bcl‐2 and inhibited the expression of the proapoptotic proteins Bax and caspase‐3.…”
Section: Regulation Of Pi3k/akt Signalling Pathway In Spinal Cord Injurymentioning
confidence: 99%
“…Nerve growth factor (NGF) is an important member of the neurotrophic factor family with important roles in neuron development, axon growth, neurotransmitter synthesis and apoptosis 220 . Xia et al 221 showed that NGF inhibited oxidative stress‐induced apoptosis in an in vitro model of SCI. NGF significantly activated the PI3K/AKT signalling pathway, promoted the expression of the anti‐apoptotic protein Bcl‐2 and inhibited the expression of the proapoptotic proteins Bax and caspase‐3.…”
Section: Regulation Of Pi3k/akt Signalling Pathway In Spinal Cord Injurymentioning
confidence: 99%
“…F Co-localization of membranes (red) and core (green) by CLSM. Adapted with permission from [ 131 ], copyright © 2022 Elsevier B.V. G Representative SDS-PAGE result showing the membrane proteins analysis of PLGA cores (lane 1), AM membranes (lane 2), AM vesicles (lane 3), TN@AM NPs (lane 4), and AM cell lysate (lane 5). Lane M: marker.…”
Section: Fabrication Of Macrophage Membrane Biomimetic Nanoparticlesmentioning
confidence: 99%
“…Good targeting capacity 3. Good behavioral and histological recovery effects [ 131 ] Acute ischemic stroke Primary macrophage MnO 2 Fingolimod In vitro: SH-SY5Y cells In vivo: rat model of transient middle cerebral artery occlusion/reperfusion 1. Actively accumulation in the damaged brain 2.…”
Section: Application Of Macrophage Membrane Biomimetic Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the above cell membranes, macrophage membranes are commonly used owing to the advantages of low immunogenicity, good biocompatibility, good biodegradability, long circulation, tendency to inflammation, and easy crossing of the blood–brain barrier. Our previous research demonstrated that macrophage-derived nanovesicles encapsulated with nerve growth factor (NGF) can play a neuroprotective role and promote the recovery of motor function after SCI [19] . Therefore, macrophage membranes-derived drug delivery carriers have high potential anti-inflammatory, neuroprotective and motor recovery applications after SCI.…”
Section: Introductionmentioning
confidence: 99%